Low-Loss Compact Silicon Nitride Arrayed Waveguide Gratings for Photonic Integrated Circuits - Kuanping Shang; Shibnath Pathak; Chuan Qin; S. J. Ben Yoo (IEEE Photonics Journal, 2017)
We report on low-loss, low-crosstalk, and compact arrayed waveguide gratings (AWGs) based on a 200-nm-thick-Si3 N4-core platform. High-resolution fabrication processes realized four types of Si3N4 AWG devices: 8 channel × 200 GHz, 16 channel × 100 GHz, 16 channel × 50 GHz, and 16 channel × 25 GHz AWGs. The insertion loss values of the four devices were 1.5 dB, 1.7 dB, 1.8 dB, and 2.7 dB; the corresponding crosstalk values were –24 dB, –21 dB, –20 dB, and –13 dB; footprints were 1.8 × 0.6 mm2, 2.2 × 0.7 mm2, 3.7 × 0.7 mm2, and 6.8 × 0.7 mm2, respectively.